2020
DOI: 10.1002/aenm.202000219
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform Ionic and Electronic Transport of Ceramic and Polymer/Ceramic Hybrid Electrolyte by Nanometer‐Scale Operando Imaging for Solid‐State Battery

Abstract: Replacing the liquid electrolyte in lithium batteries with solid‐state ion conductor is promising for next‐generation energy storage that is safe and has high energy density. Here, nanometer‐resolution ionic and electronic transport imaging of Li3PS4 (LPS), a solid‐state electrolyte (SSE), is reported. This nm resolution is achieved by using a logarithm‐scale current amplifier that enhances the current sensitivity to the fA range. Large fluctuations of ion current—one to two orders of magnitude on the LPS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…A very recent study has developed nanometer‐scale operando imaging and detected ionic current fluctuations of one to two orders of magnitude in a Li 3 PS 4 (LPS) system. [ 30 ] While the occupation ratios in the grain and GB regions captured by our simulations (for E a − GB = 0.40 eV) are of comparable magnitudes, we observed larger differences in the ion occupation ratios upon increasing the activation barrier in the GB. Results for E a − GB = 0.43 eV have been presented in Section S2 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 48%
“…A very recent study has developed nanometer‐scale operando imaging and detected ionic current fluctuations of one to two orders of magnitude in a Li 3 PS 4 (LPS) system. [ 30 ] While the occupation ratios in the grain and GB regions captured by our simulations (for E a − GB = 0.40 eV) are of comparable magnitudes, we observed larger differences in the ion occupation ratios upon increasing the activation barrier in the GB. Results for E a − GB = 0.43 eV have been presented in Section S2 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 48%
“…The spatial heterogeneity in materials properties may lead to non-uniform contact and potentially non-uniform ionic ux at electrode interface. 193 In situ AFM recently performed on a LPS/polyimine hybrid solid electrolyte found that ionic transport through the electrolyte could vary by an order of magnitude depending on where a measurement was taken. The non-uniform ionic ux was attributed to the highly complicated, tortuous pathway.…”
Section: Visualization Toolsmentioning
confidence: 99%
“…The non-uniform ionic ux was attributed to the highly complicated, tortuous pathway. 183,193 Regions with greater polymer content demonstrate less ionic and electronic current, which suggests that the dominant transport pathway was through the sulde solid electrolyte. This observation contradicts ndings on oxides, 4 and suggests that transport in these hybrid systems is highly complex and depends on the variety of factors: the polymer, the ller, the salt and the interplay between these components.…”
Section: Visualization Toolsmentioning
confidence: 99%
“…[ 293 ] With a biased probe scanning the sample surface, AFM was also used to investigate the nanoscale inhomogeneity of ionic and electronic transport in Li 3 PS 4 and its Li 3 PS 4 /polymer electrolytes. [ 294 ] The local ionic conductivity was found to differ by one to two orders‐of‐magnitude across the Li 3 PS 4 SSE. The ionic conductivity mapping indicated a sharp transition of ion transport at the boundary of polyimine/Li 3 PS 4 grains due to different grain orientations in the polycrystalline and glass ceramic materials (Figure 14c–e).…”
Section: Ec‐afm For the Understanding Of Libs And Their Materialsmentioning
confidence: 99%
“…Reproduced with permission. [ 294 ] Copyright 2020, Wiley‐VCH. f) Schematic of the in situ C‐AFM measurement on the all‐solid‐state thin‐film battery.…”
Section: Ec‐afm For the Understanding Of Libs And Their Materialsmentioning
confidence: 99%